Utilisation and costs of formal and informal care, home adaptations and physiotherapy among older patients with hip fracture - Png, ME; Griffin, XL; Costa, ML; Achten, J; Pinedo-Villanueva, R (British Editorial Society of Bone and Joint Surgery, 2020)
Aims This feasibility study investigates the utilization and cost of health resources related to formal and informal care, home adaptations, and physiotherapy among patients aged 60 years and above after hip fracture from a multicentre cohort study (World Hip Trauma Evaluation (WHiTE)) in the UK.